ANALISIS PERBANDINGAN UNJUK KERJA PROTOKOL UDP DENGAN DCCP MENGGUNAKAN TRAFIK DATA MULTIMEDIA - Adinata, Feri Setiawan; Jusak, Jusak; Sukmaaji, Anjik (Journal of Control and Network Systems, 2014)
The rapid development of network technology has created a multimedia application enters the world of internet. Skype, Yahoo Messenger, Facebook and Line are some examples of applications that provides multimedia features such as free call (VoIP) and video call (video conference) in it. Most of these applications typically use UDP instead of TCP as the transport protocol. The increased of UDP traffic has threaten TCP traffic that appears issues of fairness between the two protocols.In 2006 the IETF introduced a new protocol called Datagram Congestion Control Protocol (DCCP) CCID2 and CCID3. In fact its almost 8 years was introduced to the public, such applications are not using DCCP instead of UDP. So the question of performance, fairness and the Quality of Service level arises for multimedia data services between UDP and DCCP.Based on the results of testing against the Protocol UDP and DCCP, it is found that the average bandwidth utilization between UDP and CCID2 are respectively, 62.15% and 36.54%, the packet loss 1.12% and 10.08%, both of the delay 627 ms, both of the jitter 141 ms and both of the fairness 0.923. Furthermore, the average bandwidth utilization between UDP and CCID3 reaches 63% and 29.79%, the packet loss 0.5% and 0.92%, the delay 148ms and 283ms, the jitter 46ms and 79ms and both of the fairness 0.874. In summary, it can be concluded that the DCCP CCID2 has better performance and more suitable for VoIP/Video Conferencing instead of using the DCCP CCID3.